Biodegradable polymer drug-eluting stents versus durable polymer drug-eluting stents for percutaneous coronary intervention: a contemporary registry-based analysis. Issue 2 (28th May 2021) - Levi, Amos; Kheifets, Mark; Bental, Tamir; Perl, Leor; Codner, Pablo; Witberg, Guy; Talmor-Barkan, Yeela; Landes, Uri; Samara, Abed; Greenberg, Gabriel; Erez, Aharon; Vaknin-Assa, Hanna; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Aims: We aimed to compare the long-term outcomes of patients undergoing percutaneous coronary intervention (PCI) with biodegradable polymer drug-eluting stents (BP-DES) versus durable polymer drug-eluting stents (DP-DES). Methods and results: Among 11 517 PCIs with second-generation DES performed in our institution between 2007 and 2019, we identified 8042 procedures performed using DP-DES and 3475 using BP-DES. The primary outcome was target lesion failure, the composite target lesion revascularization (TLR), target vessel myocardial infarction and death. Propensity score matching was used to create a well-balanced cohort. Mean follow-up was 4.8 years. Of the 3413 matched pairs, 21% were females, and the mean age was 66 years. At 1 year, the primary outcome occurred in 8.3% patients versus 7.1% ( P  = 0.07), and TLR rate was 3% versus 2% ( P  = 0.006) in patients with DP-DES and BP-DES respectively. Within 5 years, the primary outcome occurred in 23.1% versus 23.4% ( P  = 0.44), and the rate of TLR was 7.2% versus 6.5% ( P  = 0.07) in patients with DP-DES and BP-DES, respectively. Conclusion: Similar rates of the composite outcome were observed throughout the entire follow-up. Target lesion revascularization rates were lower in the BP-DES group at 1-year but equalized within 5 years.